A regional economic partnership agreement between SADC and the European Union within the Cotonou framework : opportunities and challenges for the political economy of regional integration in SADC - Hengari, Alfredo Tjiurimo (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--University of Stellenbosch, 2004.